La performance del sistema educativo argentino en las últimas décadas - Analía Otero; Agustina Córica (Universidad Santo Tomás, 2017)
In the context of expansion and multiple transformations of the Argentine educational system, overﬂy discussions on institutional expansion, the evolution of the school population and samples of a system designed to generate greater inclusion. The aim of the research was to analyze the specificities of the educational status of the population of 15 to 29 year-old in recent decades. On that basis, it analyzes information available about assistance and composition of the educational system considering both the middle level and the upper level. The findings confirm the trend of an increased participation of young people in the education system together with an increase in the access to higher education levels in the first decade of the century. In this context, the socio-economic level persists as a factor in the diﬀerential educational trajectories, together with outstanding balances on educational inclusion.